Comparative Biosorption Capacity of Copper and Chromium by Bacillus Cereus - Raj A, Saravana; Muthukumar P, Vinosh; B, Bharathiraja; M, Priya (International Journal of Engineering and Technology, 2018)
Biosorption of heavy metals by bacteria is one such effective and eco-friendly method being adopted frequently for environmental applications. The present work reveals the comparative adsorption capacity of Copper and Chromium on the surface of Bacillus Cereus, aerobic, gram positive bacteria. Hexavalent chromium is toxic, non-biodegradable and persistent in nature, Copper is equally toxic when exceeds the permissible limit. Batch experimental studies were conducted in shake flask method to optimize the parameters such as pH, Reaction time, Biosorbent dose and Initial metal concentration. One of four parameters was varied keeping the other three constants and the optimum reaction time was found to be 24 hours. At an Optimum pH level of 7±2 with the optimum initial metal concentration of 100ppm the biosorption capacity was found to be 54 percent and 60 percent for Copper and Chromium respectively.